2021
DOI: 10.4149/neo_2020_200531n589
|View full text |Cite
|
Sign up to set email alerts
|

Loss of tumor intrinsic PD-L1 confers resistance to drug-induced apoptosis in human colon cancer

Abstract: Colorectal cancer (CRC) with BRAF (V600E) is associated with microsatellite instability (MSI) that predicts response to immune checkpoint inhibitors. We demonstrated the interrogation of TCGA RNA-seq human datasets revealed that BRAFV600E tumors had significantly higher Programmed Death Ligand 1 (PD-L1) mRNA compared to non-mutated BRAF CRCs. Also, MSI-H tumors were evaluated as higher PD-L1 than MSS CRCs. Inhibition of MEK/ERK by cobimetinib or CDK inhibitor dinaciclib was shown to attenuate mutant BRAF-induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…A recent study suggested that PD-L1 expression has a broader role as a potential biomarker for predicting response to immune treatment. [97] PD-L1 expression was significantly correlated with lymphatic metastasis, tumor diameter and differentiation, vascular invasion, and could act as an independent poor prognostic factor in CRC. [98] Nonetheless, the correlation between PD-L1 expression and clinicopathological features and prognosis of CRC is still controversial.…”
Section: Colorectal Cancer Biomarkers and Their Impactmentioning
confidence: 94%
“…A recent study suggested that PD-L1 expression has a broader role as a potential biomarker for predicting response to immune treatment. [97] PD-L1 expression was significantly correlated with lymphatic metastasis, tumor diameter and differentiation, vascular invasion, and could act as an independent poor prognostic factor in CRC. [98] Nonetheless, the correlation between PD-L1 expression and clinicopathological features and prognosis of CRC is still controversial.…”
Section: Colorectal Cancer Biomarkers and Their Impactmentioning
confidence: 94%
“…Additionally, a recent study has examined the relationship between PD-L1 expression and BRAF mutation [ 100 ]. Surprisingly, a high level of PD-L1 expression in MSS colorectal cancer cell lines (DiFi) was induced by BRAF V600E [ 101 ], suggesting that PD-L1 expression may not only exist in MSI-H BRAF -mutated CRC.…”
Section: Potential Biomarkers In the Tumor Immune Microenvironment Fo...mentioning
confidence: 99%
“…Feng et al manifested that oncogenic BRAF V600E in colon cancers can transcriptionally upregulate intrinsic PD-L1 expression, which enhances chemotherapy-induced apoptosis by inducing BIM and BIK proteins [ 102 ]. Subsequently, Feng et al proved the roles of c-JUN and YAP in inducing PD-L1 expression in BRAF V600E colon cancers [ 101 ]. Although PD-L1 expression fails to be a predictive biomarker for immunotherapy in colorectal cancer, the immune-independent function broadens our horizons regarding tumor therapy.…”
Section: Potential Biomarkers In the Tumor Immune Microenvironment Fo...mentioning
confidence: 99%